Spatiotemporal receptive field structures in retinogeniculate connections of cat - Suematsu, Naofumi; Naito, Tomoyuki; Miyoshi, Tomomitsu; Sawai, Hajime; Sato, Hiromichi (Frontiers in Systems Neuroscience, 2013)
The spatial structure of the receptive field (RF) of cat lateral geniculate nucleus (LGN) neurons is significantly elliptical, which may provide a basis for the orientation tuning of LGN neurons, especially at high spatial frequency stimuli. However, the input mechanisms generating this elliptical RF structure are poorly defined. We therefore compared the spatiotemporal RF structures of pairs of retinal ganglion cells (RGCs) and LGN neurons that form monosynaptic connections based on the cross-correlation analysis of their firing activities. We found that the spatial RF structure of both RGCs and LGN neurons were comparably elliptical and oriented in a direction toward the area centralis. Additionally, the spatial RF structures of pairs with the same response sign were often overlapped and similarly oriented. We also found there was a small population of pairs with RF structures that had the opposite response sign and were spatially displaced and independently oriented. Finally, the temporal RF structure of a RGC was tightly correlated with that of its target LGN neuron, though the response duration of the LGN neuron was significantly longer. Our results suggest that the elliptical RF structure of a LGN neuron is mainly inherited from the primary projecting RGC and is affected by convergent inputs from multiple RGCs. We discuss how the convergent inputs may enhance the stimulus feature sensitivity of LGN neurons.